COMPARATIVE ANATOMICAL STUDIES ON SOME SPECIES OF THE GENUS Artocarpus - Dian Palupi; Riska Desi Aryani; Sri Lestari (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
The genus Artocarpus is a member of the Moreceae family that is spread in tropical and subtropical regions, which are spread across Southeast Asia and Asia Pacific, including Indonesia. This research was conducted in ten districts in the Banyumas Regency area. Sampling of plants was done randomly selected (purposive random sampling), then the leaves were made preparations for preserved anatomy to determine the anatomical character. The data obtained from the anatomical observations were then analyzed descriptively to obtain anatomical data. There are five members of the genus Artocarpus found in the Banyumas district, namely Jackfruit (Artocarpus heterophyllus Lam.), Cempedak (Artocarpus integer (Thunb) Merr.), Breadfruit (Artocarpus altilis [Parkinson] Fosberg), Kluwih (Artocarpus camansi Blanco) and Benda (Artocarpus elasticus Reinw.exe. Ex Blume. shows anatomical variations in cuticle thickness, epidermal thickness, palisade ratio, and mesophyll thickness.